Complex palaeo-ice sheet dynamics in northeast Ireland during the retreat and reorganisation of the central British-Irish Ice Sheet - Alexander M. Clark; Bethan J. Davies; Sam Roberson; Simon P.E. Blockley; Adrian P. Palmer; Magret Damaschke (Geomorphology, 2026)

Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Making palaeoclimatology research policy‐relevant: Insights and experience from the DECADAL Project - Celia Martin‐Puertas; Laura Boyall; Alice M. Milner; Ashley M. Abrook; Amen Al‐Yaari; Alice Carter‐Champion; Daisy Fallows; Katy Flowers; Paul Lincoln; Simon Blockley; Achim Brauer; Armand Hernandez; et al. (Journal of Quaternary Science, 2026)
Quaternary palaeoclimatology uniquely provides insights and new evidence about climate variability trends and extremes prior to the instrumental record; yet, its knowledge is rarely integrated into governmental decision‐making. This opinion piece shares lessons and experience from the UKRI‐funded DECADAL project, which bridges palaeoclimate science and policy through co‐production with UK climate services and policy institutions. The views expressed represent a joint perspective of the academic and non‐academic actors involved in the project, highlighting the challenges that we faced and the solutions that we adopted. We found that an iterative collaboration through aligning research questions, outputs and formats with user needs builds trust, increases relevance and creates pathways for long‐term policy uptake. DECADAL demonstrates that engaging with relevant policy and other end‐user groups does not compromise scientific excellence; rather, it drives methodological innovation and rigour, fosters creativity and produces high‐impact, original publications that also have relevance beyond an academic audience. We argue that embedding policy engagement should be viewed as a collective community endeavour rather than the effort of an individual or research team. By embracing co‐production, palaeo‐scientists can strengthen the societal value of their research, open new avenues for innovation and collaboration, and collectively shape climate‐informed decision‐making.

A tephrostratigraphic investigation of the continuously varved Holocene Boreal lake Nautajärvi, Finland, provides precise age estimate for Lairg A/Hekla 5 eruption - Alice Carter‐Champion; Katy Flowers; Antti E.K. Ojala; Simon Blockley; Paul Lincoln; Shuang Zhang; Christina Manning; Celia Martin Puertas (Journal of Quaternary Science, 2025)
Numerous cryptotephra layers originating from Icelandic volcanoes and further afield have reached Northern Europe during the Holocene. Refining the precise timing and the relative frequency of local and distal eruptions requires well‐resolved continuous sediment archives. Lake Nautajärvi is located in central‐southern Finland (61°48′ N, 24°41′ E), and contains a continuous sequence of 9898 varves. Nautajärvi was isolated from the Baltic Sea basin at the Lake Ancylus phase ~9600 varve yr BP. We present a tephrostratigraphic record of Nautajärvi for targeted intervals within the Holocene, aiming to identify tephra from the largest eruptions, to enable an alignment with other varved lakes in Northern Europe containing tephra layers, like Diss Mere, Tiefer See and Meerfelder Maar. Geochemical analyses were produced for 26 peaks in tephra concentration, with five cryptotephra deposits corresponding to known eruptions from the mid and late Holocene. The far‐travelled KS 2 eruption from Ksudach caldera in Kamchatka is identified, enabling an alignment to Greenland, which is strengthened by the identification of the Hekla 4 tephra in Nautajärvi. Close to the KS 2 deposition in Nautajärvi, a Hekla‐type eruption correlating to the Lairg A/Hekla 5 is also identified—macroscale counting of the varves between the KS 2 and Lairg A layers enables a constrained age estimate (7001 ± 44 Cal yr BP) of the Lairg A eruption to be made. The widespread Glen Garry tephra was also identified within the Nautajärvi sequence, with an age estimate of 2088 ± 21 varve yr BP. Finally, there is also a tentative correlation to the Suduroy tephra, with an older age estimate than from the sites in which it was originally identified (8459 ± 84 varve yr BP). The remaining layers correspond to eruptions from more distal sources—several chemistries may correlate to mid‐Holocene eruptions from North America (Mount Rainier, Aniakchak, Katmai), with one shard tentatively associated with Azorean chemistry. This record provides well‐constrained age estimates for two key Holocene tephras (Glen Garry, Lairg A) and highlights the potential for far‐travelled tephras from North America and Kamchatka to reach Northern Europe, emphasising the benefits of further tephra studies in Scandinavia.

Holocene climate evolution and human activity as recorded by the sediment record of lake Diss Mere, England - Laura Boyall; Celia Martin‐Puertas; Rik Tjallingii; Alice M. Milner; Simon P. E. Blockley (Journal of Quaternary Science, 2024)
Lake sediments are ideal archives to evaluate the interactions between climatically driven environmental responses and human activity on seasonal to multi‐decadal timescales. This study focuses on the unique sediments of Diss Mere, the only lake in England providing an annually laminated (varved) record for most of the Holocene. We combine microfacies analysis with X‐ray core scanning data to explore the influence of natural and human‐led changes on sediment deposition over the past 10 200 years and evaluate the sensitivity of the lake sediments to climate variability through time. Variability of titanium (Ti), calcium (Ca) and silica (Si) explain most of the lithological changes observed in the sediment and we identify three stages with low (10 290–2070 cal a bp ), intermediate (2070–1040 cal a bp ) and intensified (1040 cal a bp – present) human influence. During the first stage, where varved sediments are preserved, Ti is low due to the minimal detrital input into the lake. Ca and Si during this stage reveal high‐amplitude variability responding to seasonal changes in sediment deposition. The termination of varved sediment preservation and increases in sedimentation rates coincide with a major rise in Ti after this first stage, marking the intensification of human activity around the lake. Ca is used here as an indicator of temperature‐included calcite precipitation, and the long‐term variability of the Ca profile resembles Holocene temperature evolution. This continues during periods of intensified human activity, suggesting that the Diss Mere sediments remain sensitive to climate through time.

Distal tephra reveal new MIS 5e Kos eruptions: Implications for the chronology and volcanic evolution histories in the Eastern Mediterranean region - Shuang Zhang; Simon Blockley; Simon J. Armitage; Chris Satow; Christina Manning; Omry Barzilai; Elisabetta Boaretto; Dustin White; Rhys Timms (Quaternary Science Reviews, 2023)

Updated age constraints on key tephra markers for NW Europe based on a high-precision varve lake chronology - Amy A. Walsh; Simon P.E. Blockley; Alice M. Milner; Celia Martin-Puertas (Quaternary Science Reviews, 2023)

Reconstruction of short-term storm surge-driven increases in shallow coastal lake salinity using ostracod shell chemistry - Lucy R. Roberts; Jonathan A. Holmes; David J. Horne; Melanie J. Leng; Carl D. Sayer; Rhys G. O. Timms; Katy Flowers; Simon P. M. Blockley; Andrea Kelly (Natural Hazards, 2022)

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Temporal patterns in lacustrine stable isotopes as evidence for climate change during the late glacial in the Southern European Alps - Walter Finsinger; Claudio Belis; Simon P. E. Blockley; Ueli Eicher; Markus Leuenberger; André F. Lotter; Brigitta Ammann (Journal of Paleolimnology, 2008)